iTeaching for uLearning : Interactive Teaching Tools for Ubiquitous Learning in Higher Education - Chuah, Kee Man (AKEPT, UKM Bangi, 2015)
The shift of focus to learner-centred approaches in teaching and learning has intensified the increasing use of technological tools in the classrooms. Educators are no longer restricted to the use of traditional teaching resources or materials, but are showered with various technological advancements that enhance the learning experience. Such shift in technological development demands a change in the traditional pedagogy that used to be the epitome of teaching and learning. Hence, interactive teaching (iTeaching) methods are regarded as the much-needed boost for 21st century learning environments in which learners are given more autonomy in their learning process.